PENGARUH KARAKTERISTIK KOMITE AUDIT PADA KONDISI FINANCIAL DISTRESS PERUSAHAAN, STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2008 – 2010 - Martina Eny Kristanti; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2012)
This study aims to analyze the influences of audit committee characteristics, consisted of audit committee size, independent commissioners of audit committee, audit committee meeting frequency, and financial competence of audit committee members, to the possibility of financial distress in companies. Data used in this study were drawn from financial statements and annual reports of listed manufacturing companies in Indonesia Stock Exchange (IDX) during 2008-2010. This study used logistic regression analysis to examine the effect of audit committee size, independent commissioners of audit committee, audit committee meeting frequency, and financial competence of audit committee members on company's financial distress condition. The results of this study indicate: 1) audit committee size does not have  significant influence on the probability of company's financial distress, 2) audit committee independence does not have significant influence on the probability of company's financial distress, 3) audit committee meeting frequency provides  negative significant influence on the probability of company's financial distress,  companies that have more often meeting frequency, have less probability to encounter financial distress, and 4) financial competence of audit committee members does not have significant influence on the probability of company's financial distress.